Improving communication between postgraduate researchers and the university library: a case study at De Montfort University Library and Learning Services - Petch, Melanie; Fraser, Katie; Rush, Nathan; Cope, Alan; Lowe, Julie (Taylor & Francis, 2016)
A well-established postgraduate researcher development program has existed at De Montfort University for many years. Library and Learning Services include modules on literature searching skills and critical appraisal. However, we recognized that researchers seemed to be disengaged with the services on offer. This concern informed a research project that considered the ways we could communicate better with researchers based on their needs. This paper explores the essential components of successful communication, such as context, timeliness and communication channels. An action-research approach was taken including focus groups and online surveys. The outcomes highlighted three significant crisis points, emphasizing the key times when researchers might need some intervention. The findings of this research identified the distinct needs of Postgraduate Researchers (PGRs) and how relevant and timely communication from the library can meet these needs. It also considers the impact of how communication has improved with researchers as a result of some of our interventions.